Un roi Sheshonq à Hermopolis - el-Dine, Hassan Nasr.
The subject of this paper is a piece of faience, restored at the Ashmounein magazine in Middle Egypt. This piece contains hieroglyphic inscriptions that mention the name and titles of a king Sheshonq. This is the only document that preserves the names and titles of that Libyan king at Touna el-Gebel.